1977
DOI: 10.1083/jcb.74.3.828
|View full text |Cite
|
Sign up to set email alerts
|

Elemental distribution in striated muscle and the effects of hypertonicity: Electron probe analysis of cryo sections

Abstract: A method of rapid freezing in supercooled Freon 22 (monochlorodifluoromethane) followed by cryoultramicrotomy is described and shown to yield ultrathin sections in which both the cellular ultrastructure and the distribution of diffusible ions across the cell membrane are preserved and intracellular compartmentalization of diffusible ions can be quantitated. Quantitative electron probe analysis (Shuman, H., A. V. Somlyo, and A. P. . Ultramicros. 1:317-339.) of freeze-dried ultrathin cryo sections was found to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(190 citation statements)
references
References 70 publications
14
173
3
Order By: Relevance
“…skeletal muscle (Somlyo et al, 1977). Again, there was no increase in mitochondrial C a and only a modest but statistically significant rise in cytoplasmic total C a.…”
Section: Dendritic Endoplasmic Reticulum Is the Major Calcium Sequestmentioning
confidence: 83%
See 3 more Smart Citations
“…skeletal muscle (Somlyo et al, 1977). Again, there was no increase in mitochondrial C a and only a modest but statistically significant rise in cytoplasmic total C a.…”
Section: Dendritic Endoplasmic Reticulum Is the Major Calcium Sequestmentioning
confidence: 83%
“…EDX analysis of both preparations revealed that the concentrations of total C a, as well as of other elements, in the three target compartments of CA3 apical dendrites (Table 1) were comparable to basal concentrations in other excitable and nonexcitable cells (Somlyo et al, 1977(Somlyo et al, , 1985Andrews et al, 1988). The mean concentration of Ca within dendritic ER was 5.1 Ϯ 1.1 mmol/kg dry weight (mean Ϯ SEM; Table 1), although, as discussed below, this morphologically identified set of ER consists of at least two functionally distinct populations that, under basal conditions, coincidentally display similar low Ca concentrations.…”
Section: Basal Elemental Concentrations In Dendritic Compartmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, until recently, the question of whether the SR of resting muscle is a truly intracellular compartment or one in ionic communication with and similar in ionic contents to the extracellular space was the subject of some debate (for review, see references 74,96) . The availability of electron-probe microanalysis at high spatial resolution combined with rapid freezing techniques to preserve the in vivo distribution of diffusible elements (for review, see references 39,44,59,60,93) made it possible to measure the inorganic content of cell organelles in situ .…”
mentioning
confidence: 99%